Influence of Internet Addiction on Pre-Service Mathematics Teachers' Learning and Motivation in Nigerian South-West Universities - Sabainah Oyebola Akinoso (Babes-Bolyai University, 2023)
The widespread use of the internet has led to a growing concern about the impact of internet addiction on pre-service Mathematics teachers' learning. This paper investigates the impacts of internet addiction on the learning and professional development of pre-service Mathematics teachers. The population covers the undergraduate Mathematics education students from public universities in south-west Nigeria. The sample was randomly selected from 100 to 400 levels while the sample size was 200 pre-service teachers across the levels from one selected university. A well-structured questionnaire was used to get data from pre-service Mathematics teachers on internet addiction. This study employed a descriptive and inferential research design to create responses to the research questions. The data collected were analysed using mean and standard deviation for the two research questions while Pearson Product Moment Correlation Coefficient was used to test the hypothesis raised. There is a significant relationship between internet addiction and Mathematics learning. This yields a positive result that, the students who access the internet more frequently learn more effectively and highly motivated in learning Mathematics. It was suggested that the internet can be a useful tool for learning but must be used responsibly. However, addressing internet addiction through education, prevention, and intervention efforts should be integrated into the teacher education program to support pre-service mathematics teachers in developing healthy internet use habits and maintaining high levels of motivation to learn.